Analysis of Environmental, Social and Economic Conditions of the Ecosystem Restoration Area of PT. The Best One Unitimber Kampar Peninsula - Bambang Dewo Bagus; Ridwan Manda Putra; Zulkarnain Umar (Berkala Perikanan Terubuk, 2023)
Kampar Peninsula ecosystem restoration activity by PT. The Best One Unitimber has the potential to create an innovative and creative conservation and protection of the peat swamp forest ecosystem in the Kampar Peninsula, namely establishing support from the private sector to increase the ability to maintain the peat swamp forest ecosystem, both physically and socially and economically. Given the huge potential of the Kampar Peninsula ecosystem restoration area by PT. The Best One Unit, it is necessary to carry out an in-depth analysis of its environmental, social and economic conditions. The purpose of this study was to analyze the environmental, social and economic conditions of the Kampar Peninsula ecosystem restoration area by PT. The Best One United. The environmental conditions observed consisted of land cover change data, vegetation and fauna data. While socio-economic data were obtained directly by observation (direct observation) and in-depth interviews with the people living around the concession and interacting with the IUPHHK-RE area of PT. The Best One Unit in Pelalawan Regency. The results showed that the Kampar Peninsula ecosystem restoration area by PT. The Best One Unitimber has high natural resources, as evidenced by the changing conditions of land cover, the diverse potential of vegetation and fauna in it. Not only environmental conditions, but socio-economic conditions which are also very closely related to environmental conditions in the Kampar Peninsula ecosystem restoration area by PT. The Best One United.